2014
DOI: 10.3329/bjas.v43i2.20714
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flooring and rearing system on hoof health of dairy cows in some selected areas of Bangladesh

Abstract: A survey was conducted to explore prevalence and risk factors of diverse hoof disorders on dairy cows at Chittagong and Patuakhali, Bangladesh from June 2012 to February 2013. About 2103 cows were examined from where 497 cases identified having fissure (37%), crack (19%), partially broken (19%), swollen hoof (16%) and multiple disorders (9%) in backyard dairy cows whereas 37%, 17%, 20%, 20% and 6% in commercial cows, respectively. Significantly higher prevalence (p<0.05) was recorded in cows reared under co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The cow prevalence of lameness of 19.1% with herd prevalence ranging from 10 to 33% reported in this study is similar to that presented in Bangladesh and China (Rahman et al 2014 ; Chapinal et al 2014 ) and different from that reported in Switzerland and Ireland (Becker et al 2014 ; Somers and O’Grady 2015 ). The disparity could be due to variation in herd size, management practices, and diagnostic criteria (Tadich et al 2010 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The cow prevalence of lameness of 19.1% with herd prevalence ranging from 10 to 33% reported in this study is similar to that presented in Bangladesh and China (Rahman et al 2014 ; Chapinal et al 2014 ) and different from that reported in Switzerland and Ireland (Becker et al 2014 ; Somers and O’Grady 2015 ). The disparity could be due to variation in herd size, management practices, and diagnostic criteria (Tadich et al 2010 ).…”
Section: Discussionsupporting
confidence: 86%
“…Lameness in dairy cows is a welfare problem (Whay and Shearer 2017 ) and causes economic loss attributed to early culling, treatment, of and reduced milk yield (Green et al 2014 ; Thomas et al 2016 ). The prevalence of lameness varies amongst herds between regions and countries as cow level prevalence of lameness was 21.98 and 18.9% in western Thailand (Rahman et al 2014 ) and Australian dairy herds, respectively (Ranjbar et al 2016 ). In India, a recent study reported incidence of lameness of 17.2% in contrast to 9.4% recorded previously (Asit and Pankaj 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The alteration on movement parameters that this surface generates, given its high abrasion and the discomfort it causes to the animal, makes the use of this surface in free housing of dairy cows not recommended. This situation is confirmed with a high prevalence of lameness, which fluctuates between 13.3% and 40.9% [ 33 , 35 , 36 ], Figure 4 A.…”
Section: Resultsmentioning
confidence: 62%
“…The bovine lameness prevalence range on rubber surfaces is between 5% and 27.9% [ 22 , 35 , 68 , 69 , 70 , 74 , 75 ]. Most studies report values around 20% ( Figure 4 A, Table S1 ) as well as a lower annual milk production than that of sand (11027 ± 240 kg/cow/year, n = 119 vs. 11785 ± 240 kg/cow/year, n = 89) [ 24 ], with no significant difference to the one reported for hard and abrasive surfaces such as asphalt (7535 ± 745 kg/cow/year, n = 193 vs. 7286 ± 1778 kg/cow/year, n = 239) and concrete (7535 ± 745 kg/cow/year, n = 193 vs. 7889 ± 1179 kg/cow/year, n = 213) [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation